Design and Synthesis of Novel Hybrid Benzamide-Peptide Histone Deacetylase Inhibitors - Hu, Fang (2009)
We designed and synthesized a series of novel hybrid histone deacetylase inhibitors based on conjugation of benzamide-type inhibitors with either linear or cyclic peptides. Linear tetrapeptides (compounds 13 and 14), cyclic tetrapeptides (compounds 1 and 11), and heptanediamide-peptide conjugates (compounds 10, 12, 15 and 16) were synthesized through on-resin solid-phase peptide synthesis (SPPS). All compounds were found to be moderate HDAC1 and HDAC3 inhibitors, with IC50 values ranging from 1.3 µM to 532 µM. Interestingly, compound 15 showed 19-fold selectivity for HDAC3 versus HDAC1.